Petunia as a model for MYB transcription factor action under salt stress - Zepeda, Baltasar; Marcelis, Leo F. M.; Kaiser, Elias; Verdonk, Julian C. (Frontiers in Plant Science, 2023)
Salinity is a current and growing problem, affecting crops worldwide by reducing yields and product quality. Plants have different mechanisms to adapt to salinity; some crops are highly studied, and their salinity tolerance mechanisms are widely known. However, there are other crops with commercial importance that still need characterization of their molecular mechanisms. Usually, transcription factors are in charge of the regulation of complex processes, such as the response to salinity. MYB-TFs are a family of transcription factors that regulate various processes in plant development, and both central and specialized metabolism. MYB-TFs have been studied extensively as mediators of specialized metabolism, and some are master regulators. The influence of MYB-TFs on highly orchestrated mechanisms, such as salinity tolerance, is an attractive research target. The versatility of petunia as a model species has allowed for advances to be made in multiple fields: metabolomic pathways, quality traits, stress resistance, and signal transduction. It has the potential to be the link between horticultural crops and lab models, making it useful in translating discoveries related to the MYB-TF pathways into other crops. We present a phylogenetic tree made with Petunia axillaris and Petunia inflata R2R3-MYB subfamily sequences, which could be used to find functional conservation between different species. This work could set the foundations to improve salinity resistance in other commercial crops in later studies.